Consumer comfort and its role in relationship marketing outcomes: an empirical investigation - Gaur, SS; Madan, S; Xu, Y (Association for Consumer Research, 2009)
Our study contends that relationship comfort has a positive impact on various relationship marketing outcomes namely, satisfaction, trust, commitment, loyalty and active voice. We investigate if consumer relationship proneness moderates the impact of relationship comfort on various relationship marketing outcomes by using SEM and multi-group analysis on primary data collected from 300 respondents in India. Our findings demonstrate that relationship comfort has a positive impact on relationship marketing outcomes, and confirm that consumer relationship proneness moderates the link between relationship comfort and relationship marketing outcomes.
Keywords: Relationship comfort; Relationship marketing